2016
DOI: 10.1017/s1472669616000384
|View full text |Cite
|
Sign up to set email alerts
|

Law Student Views on the Principles of a Legal Research Website: a User Experience Study

Abstract: Abstract:The Principles of Legal Research Website of the University of Ottawa's Brian Dickson Law Library is a bilingual (English and French) online learning tool for all first year students in both Common Law and Civil Law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A navigation system design should be a customized way that enables users to access information without stress. Information architecture is the core component of a website and, thus, it should help interweave a web page and not get frustrated [27]. Universities' libraries are outlets of bulk materials.…”
Section: A Correlation Between the Results Of Heuristic Evaluation And Task-based Usability Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A navigation system design should be a customized way that enables users to access information without stress. Information architecture is the core component of a website and, thus, it should help interweave a web page and not get frustrated [27]. Universities' libraries are outlets of bulk materials.…”
Section: A Correlation Between the Results Of Heuristic Evaluation And Task-based Usability Testingmentioning
confidence: 99%
“…Saudi Digital Library results revealed that this arrangement has promoted awareness of academic literature, which, in turn, has contributed to the realization of increased learning opportunities [20]. Navigation systems should enhance the users' capacity to identify particular data without necessarily taking a substantial amount of time to locate them [27]. The criterion for recognition rather than recall is the provision of guidance to navigate a system easily through recognition and recall attributes.…”
Section: A Correlation Between the Results Of Heuristic Evaluation And Task-based Usability Testingmentioning
confidence: 99%
“…However, law libraries also face some challenges with social media. According to Intahchomphoo et al (2016) 3 research shows that the majority of law students, who participated in their elearning research, do not wish to see social media functionalities being implemented in their law library's legal research website. The authors posit that law students think of social media as something to be used for personal socialization with their friends and not as something to be used in their academic online environments.…”
Section: Introductionmentioning
confidence: 99%